Phorbol esters isolated from Jatropha meal induced apoptosis-mediated inhibition in proliferation of Chang and Vero cell lines - Oskoueian, Ehsan; Abdullah, Norhani; Ahmad, Syahida (MDPI, 2012)
The direct feeding of Jatropha meal containing phorbol esters (PEs) indicated mild to severe toxicity symptoms in various organs of different animals. However, limited information is available on cellular and molecular mechanism of toxicity caused by PEs present in Jatropha meal. Thus, the present study was conducted to determine the cytotoxic and mode of action of PEs isolated from Jatropha meal using human hepatocyte (Chang) and African green monkey kidney (Vero) cell lines. The results showed that isolated PEs inhibited cell proliferation in a dose-dependent manner in both cell lines with the CC50 of 125.9 and 110.3 μg/mL, respectively. These values were compatible to that of phorbol 12-myristate 13-acetate (PMA) values as positive control i.e., 124.5 and 106.3 μg/mL respectively. Microscopic examination, flow cytometry and DNA fragmentation results confirmed cell death due to apoptosis upon treatment with PEs and PMA at CC50 concentration for 24 h in both cell lines. The Western blot analysis revealed the overexpression of PKC-δ and activation of caspase-3 proteins which could be involved in the mechanism of action of PEs and PMA. Consequently, the PEs isolated form Jatropha meal caused toxicity and induced apoptosis-mediated proliferation inhibition toward Chang and Vero cell lines involving over-expression of PKC-δ and caspase-3 as their mode of actions.